Towards a Definition of Time in Archaeology: French Prehistoric Archaeology (1850-1900) - Oscar Adadia (Papers from the Institute of Archaeology, 2002)
This paper presents a critical reflection on time in the field of the history of archaeology. For historians of archaeology, the analysis of time is frequently assimilated into the examination of different ‘chronologies’ and the presentation of the development of dating techniques. However, this article argues that it is possible to conceptualise time as an historical concept which has been defined by shape, function, context and some a priori ideas. This paper discusses some of the key notions through which archaeologists conceptualised time in the second half of the 19th century. These ideas are essential in allowing us to understand not only the later development of the discipline, but also our interpretation of the past in general.
Keywords: Prehistory; History of Archaeology; France